ANALISIS KONFLIK ANTARA INDONESIA DENGAN TIMOR LESTE : SENGKETA PERBATASAN DARAT - Berliana Fatihatuz Fiizha (SINDANG: Jurnal Pendidikan Sejarah dan Kajian Sejarah, 2021)
Abstract Disputes are things that cause disputes and debates that eventually lead to conflict and usually start from small problems which then lead to serious problems. For example, the conflict that occurred between Indonesia and Timor Leste was caused by a land border dispute between the two countries. The territory of the State of Indonesia has many borders with neighboring countries, both land and sea. In general, people in border areas often experience conflicts that are motivated by seizure of land power from each country. In analyzing the problems in the article, the writer uses the literature study method to support the quality of the article. The land border between Indonesia and Timor Leste is divided into 2 sectors or segments, namely the Unsurveyed segment and the Unresolved segment. The areas included in the Unsurveyed segment are the Oben segment to the Subina segment with an area of ​​approximately 14 Km located in Bikomi Nilulat District, North Central Timor Regency and consisting of 6 villages, among others, Sunkaen, Inbate, Nainaban, Nilulat, Haumeniana and Body. While the areas that are included in the Unresolved segment are those in Manusasi Village, Bijaelsunan, Miomaffo Timur District, North Central Timor Regency. Keywords: Territorial disputes, Land borders, Conflicts between communities